Ambulatory anaesthesia and cognitive dysfunction. Issue 6 (December 2015) - Rasmussen, Lars S.; Steinmetz, Jacob
Abstract : Purpose of review: More surgical procedures are performed on an ambulatory basis and the advantages are apparent, but outpatient surgery presents challenges because of the expectation of a fast recovery soon after termination of anaesthesia. Ambulatory surgery is a well tolerated regimen with few serious adverse outcomes, hence difficult to obtain sound scientific evidence for avoiding complications. Recent findings: Few studies have assessed recovery of cognitive function after ambulatory surgery, but it seems that both propofol and modern volatile anaesthetics are rational choices for general anaesthesia in the outpatient setting. Cognitive complications such as delirium and postoperative cognitive dysfunction are less frequent in ambulatory surgery than with hospitalization. Summary: The elderly are especially susceptible to adverse effects of the hospital environment such as immobilisation, sleep deprivation, unfamiliar surroundings, and medication errors. Enhanced recovery programmes (fast-track regimens) may allow earlier discharge which is probably beneficial for the elderly. Frailty is becoming an increasingly important concept that needs to be clinically considered in elderly patients, as well as in future studies.